Analisis Pelayanan Staf Unit Lost and found dalam Menangani Permasalahan Delay Baggage pada Penumpang Singapore Airlines di Bandar Udara Internasional Juanda Surabaya - Aprilia, Chintia Ariesta Bina; Putrie, Annike Resty (VISA: Journal of Vision and Ideas, 2024)
Delay baggage is one of the issues handled by the lost and found unit at the airport. This happens when the baggage arrives late at the destination airport, especially on international flights. Some factors that contribute to delay baggage are short connecting flight times, baggage label detachment, and loading errors. This research aims to find out how the staf at the lost and found unit handle delay baggage issues for Singapore Airlines at Juanda Surabaya International Airport. The research method used is descriptive qualitative with interviews, observations, and documentation as data collection methods. The data obtained from this research includes interview results with the staf at the lost and found unit, as well as documents used in their daily activities. The results show that the service provided by the staf at the lost and found unit to Singapore Airlines passengers experiencing delay baggage issues is in accordance with Standard Operational Procedure (SOP). This includes baggage search and retrieval, as well as compensation provided by the airline.